Integrated approach for lineament extraction in assessing groundwater potential: a case study in the highlands of Eritrea - Asghede, Kabral Mogos; Vágó, János; Pecsmány, Péter (Acta Geographica Debrecina Landscape & Environment series, 2025)
Groundwater exploration is crucial for sustaining ecosystems and human activities, particularly in semi-arid regions like the highlands of Eritrea. This study evaluates the effectiveness of manual and automated lineament extraction methods for identifying geological structures indicative of groundwater potential. Using a 30-meter resolution SRTM digital elevation model (DEM), we generated hillshade images and extracted lineaments manually by ESRI ArcGIS and automatically with MATLAB’s edge detection algorithms, including Canny, Sobel, Prewitt, Roberts, Approximate Canny, and Laplacian of Gaussian (LoG). Our findings reveal significant differences between the manual and automated methods. Directional analysis showed that manually identified lineaments primarily followed NE-SW and NW-SE directions. Among the automated methods, Canny, Approxcanny, and Prewitt exhibited similar directional trends. Lineament density maps indicated high-density areas in the western and northern parts of the study area for both manual and automated methods. The LoG algorithm showed the highest correlation (0.8561) with the manual method, suggesting it as a reliable alternative for lineament mapping, contributing to more efficient groundwater exploration in semi-arid regions.